Influence of Substrate Bias Voltage on Structure and Properties of (AlCrMoNiTi)N Films - Xue Gao; Bin Li; Yiman Zhao; Xunwang Shi; Yujie Chen; Bin Liao; Erzhou Ren (Nanomaterials)
(AlCrMoNiTi)N high-entropy alloy nitride (HEAN) films were synthesized at various bias voltages using the co-filter cathodic vacuum arc (co-FCVA) deposition technique. This study systematically investigates the effect of bias voltage on the microstructure and performance of HEAN films. The results indicate that an increase in bias voltage enhances the energy of ions while concomitantly reducing the deposition rate. All synthesized (AlCrMoNiTi)N HEAN films demonstrated the composite structure composed of FCC phase and metallic Ni. The hardness of the (AlCrMoNiTi)N HEAN film synthesized at a bias voltage of −100 V attained a maximum value of 38.7 GPa. This high hardness is primarily attributed to the synergistic effects stemming from the formation of strong metal-nitrogen (Me-N) bonding formed between the target elements and the N element, the densification of the film structure, and the ion beam-assisted bombardment strengthening of the co-FCVA deposition technique. In addition, the corrosion current density of the film prepared at this bias voltage was measured at 4.9 × 10−7 A·cm−2, significantly lower than that of 304 stainless steel, indicating excellent corrosion resistance.